2004
DOI: 10.1080/09553000410001702319
|View full text |Cite
|
Sign up to set email alerts
|

Induction of reproductive cell death and chromosome aberrations in radioresistant tumour cells by carbon ions

Abstract: An increased biological efficiency of carbon ions could be confirmed in radioresistant tumour cells with respect to the induction of reproductive cell death and of unstable as well as stable chromosome aberrations. Relative biological effectiveness reached 2.9 for cell killing by carbon ions from the extended Bragg peak. The yields of apparently simple dicentrics as well as of total dicentrics, i.e. simple dicentrics plus dicentrics belonging to complex exchanges, evaluated in Giemsa-stained metaphases as obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, repair kinetics (investigated at later time points) have shown a delayed or less successful repair of DSBs after high-LET radiation ( 16 , 17 ). Therefore, particle irradiation can be effective in inducing cell death even in highly radioresistant cells ( 18 ). One of the factors that plays a major role in determining radiosensitivity is p53.…”
Section: Introductionmentioning
confidence: 99%
“…However, repair kinetics (investigated at later time points) have shown a delayed or less successful repair of DSBs after high-LET radiation ( 16 , 17 ). Therefore, particle irradiation can be effective in inducing cell death even in highly radioresistant cells ( 18 ). One of the factors that plays a major role in determining radiosensitivity is p53.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [21, 34, 35, 46] have reported linear relationships between foci numbers or relative γ-H2AX fluorescence and dose using X-rays but generally at high doses. Using a series of cancer cell lines, it was concluded that the presence of γ-H2AX foci at long times after γ-irradiation of exponentially growing monolayers may not always signify the presence of a DSB [38].…”
Section: Introductionmentioning
confidence: 99%
“…These results are well in line with findings of Hofman-Huther et al . (2004) who observed that the frequencies of cells containing complex chromosomal aberrations increased dramatically after irradiation of radio-resistant tumor cells with carbon ions versus X-rays [46]. One decade earlier, it was demonstrated that dense ionizing radiation, such as heavy ions, is much more efficient than sparsely ionizing radiation in the induction of complex-type exchanges [47].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, higher amounts of basal DNA damage, as evidenced by an increase in the number of basal γ -H2AX foci is often observed in different types of tumors ( Warters et al, 2005 ; Bonner et al, 2008 ). A dramatic increase in the frequency of complex CAs in radio-resistant tumor cells was observed after carbon ion irradiation ( Hofman-Huther et al, 2004 ). Subsequent cytogenetic studies revealed exposure to HZE radiation can cause a much higher level of complex chromosomal rearrangements ( Loucas and Cornforth, 2001 ; Durante et al, 2002 ).…”
Section: Dna Damage Response Focimentioning
confidence: 99%